Impacto do estilo de condução no consumo de combustível e nas emissões veiculares - Bernardo Junqueira Murta (2018)
The automobile industries are, globally, one of the biggest responsible for CO2 and NOX emissions, contributing with 47,5% of Brazilians energy sector emissions. In fact, reducing vehicle emissions is primordial for countries to achieve their National Determined Contribution (NDC), set by the Paris Agreement, in December 2015. With this goal, in this work it was studied gear shift times influences on vehicle emissions and fuel consumption increase, related to drivers way of driving. Tests were held considering tree gear shift strategies: following a gear shift indicator (GSI) set by FCA; an alternative GSI, proposed for the developed system with OBD-II data monitoring; and random gear shifts, without a specific gear shift strategy. All fuel consumption and emissions results were compared with data obtained when following the vehicle standard GSI available. For this case, the tests without the use of the gearshift indicator obtained a mean worsening in fuel consumption of 0.5% for the urban case and 0.06% for the highway test. The most consuming test obtained an increase of 3.0% for the urban case and 0.7% for the highway test. In relation to CO2 emissions, an increase of approximately 1% was obtained when not following the GSI suggestion. With the developed OBD-II data acquisition system, an alternative GSI strategy was integrated into the code, which tests increased consumption in about 0.75% and 0.33% for the urban and highway tests respectively, representing an improvement by comparing with the most consuming case, with no gear shift information. This work, therefore, showed the importance of following gear shift strategies in order to reduce in fuel consumption and vehicular emissions. In this way, embedded systems to allow feedback suggestions to the user, as proposed, become a low cost and important solution to obtain improvements in energy efficiency and to reduce the greenhouse effect